Bushes and bullets: illegal cocaine markets and violence in Colombia (2013)
This paper proposes a new identification strategy to estimate the causal impact of illicit drug markets on violence using a panel of Colombian municipalities covering the period 1994-2008. Using a UNODC survey of Colombian rural households involved in coca cultivation, we estimate the determinants of land suitability for coca cultivation. With these results we create a suitability index that depends on the altitude, erosion, soil aptitude, and precipitation of a municipality. Our exogenous suitability index predicts the presence of coca crops cross sectionally and its expansion between 1994-2000. We show that following an increase in the demand for Colombian cocaine, coca cultivation increases disproportionately in municipalities with a high suitability index. This provides an exogenous source of variation in the extent of coca cultivation within municipalities that we use as an instrument to uncover the causal effect of illegal cocaine markets on violence. We find that a 10% increase in the value of coca cultivation in a municipality increases homicides by about 1.25%, forced displacement by about 3%, attacks by insurgent groups by about 2%, and incidents involving the explosion of land mines by about 1%. Our evidence is consistent with the view suggesting that prohibition creates rents for suppliers in illegal markets, and these rents cause violence as different armed groups fight each other, the government and the civil population for their control and extraction.